Sequential application of bio-pesticide, botanical and chemical insecticide to manage aphid and pod borer attacking yard long bean (Bangladesh Journal of Agricultural Research, 2017)
Present study evaluated the effect of sequential application of a bio-pesticide (Bacillus thuringiensis subsp. Kurstaki) (Bt), a botanical (neem oil) and a chemical insecticide (cypermethrin 25EC) as well as cypermethrin 25EC alone in the management of aphid (Aphis craccivora) and pod borer (Maruca vitrata) attacking yard long bean (Vigna unguiculata sesquipedalis) in the field. In each treatment Bt, neem oil and cypermethrin were applied in alternative sequence as well as cypermethrin alone at 07 days intervals. All the treatments reduced aphid population and flower infestation after 24, 48 and 72h of treatment compared to untreated control. Aphid population reduction by the treatments over control was ranged from 34.4 to 71.9%, and the treatment with cypermethrin alone had the lowest abundance of aphid and flower infestation. The Bt followed by neem oil and cypermethrin significantly reduced the pod infestation by pod borer and increased yield (38.9–41.4%) over control with BCR: 1.85-2.16. Use of cypermethrin alone was most effective and showed the lowest pod infestation and revealed the increased yield over control (47.7%) with BCR 4.70. Considering the hazardous affect of cypermethrin alone, its application followed by bio-pesticide and botanical sequentially would be promising components for integrated pest management strategies against aphid and pod borer attacking yard long bean.Bangladesh J. Agril. Res. 42(3): 531-538, September 2017